Morphological and biochemical studies of the milt (Spermatozoa) of the snow-trout fish Schizothorax richardsonii (Gray) - S. N. Bahuguna; Amit K. Tripathi; Amir Khan (Environment Conservation Journal, 2011)
The present study was undertaken to evaluate the biochemical and morphological nature of the milt (=spermatozoa) of the snow-trout fish Schizothorax richardsonii. The study was conducted to find out the possibilities of evolving cryopreservation, artificial propagation for better fishery development. Scanning Electron Microscopy was employed to find out the structural details of the sperm cell. Biometric and mobility studies were also done on the sperm cells to obtain their sizes and movements. The present findings showed that S. richardsonii has high protein and lipid content in gonads. The spermatozonic characteristics of these fishes can help in maintaining stocks of their populations in natural aquaculture resources.